2010
DOI: 10.1007/bf03347080
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased parathyroid hormone with neuroendocrine activation and endothelial dysfunction in elderly men with heart failure

Abstract: High PTH levels have been reported in patients with chronic heart failure (CHF). Similarly, its levels increase with aging and are related to impaired survival in elderly adults. However, its relationship with neuroendocrine activation and endothelial dysfunction in CHF has not been previously studied. Seventy-three CHF males with New York Heart Association (NYHA) classes II and III and 20 control subjects aged ≥ 55 yr were recruited. PTH, 25-hydroxyvitamin D [25(OH)D], N-terminal pro-brain natriuretic peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
3
24
1
Order By: Relevance
“…Recently, parathyroid hormone (PTH), which acts to increase calcium concentration by activating the parathyroid hormone receptor (PTHR), has been implicated in myocardial hypertrophy (27). Elevated PTH has been reported in patients with chronic heart failure (25) with an acceleration of a decompensation of the left ventricle, evidenced by reduced fractional shortening and posterior wall thickness, observed in PTH-treated mice (7). In this study, males consuming ethanol demonstrated an increase in PTH 2 receptor.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, parathyroid hormone (PTH), which acts to increase calcium concentration by activating the parathyroid hormone receptor (PTHR), has been implicated in myocardial hypertrophy (27). Elevated PTH has been reported in patients with chronic heart failure (25) with an acceleration of a decompensation of the left ventricle, evidenced by reduced fractional shortening and posterior wall thickness, observed in PTH-treated mice (7). In this study, males consuming ethanol demonstrated an increase in PTH 2 receptor.…”
Section: Discussionmentioning
confidence: 59%
“…Fourth, PTH is associated with cardiovascular risk factors in the general population 29,73,102,103. Increased PTH levels are associated with hypertension,31,104109 CAD,34,73,102 left ventricular hypertrophy,110,111 cardiac arrhythmias,112 heart failure,30,33,110,113116 and insulin sensitivity,117 as well as cardiovascular and all-cause mortality in patients with87,118,119 and without chronic kidney disease 29,32,43,70,78,79,120122…”
Section: Discussionmentioning
confidence: 99%
“…PTH may therefore serve a role in the pathophysiology of cardiovascular disease (13). A series of previous studies (14,15) have suggested that PTH may directly induce endothelial dysfunction and contribute to VC. However, the underlying mechanisms of this remain unclear.…”
Section: Introductionmentioning
confidence: 99%